Uso de la cefalexina en infecciones piogenas de la piel: comparacion de dos esquemas terapeuticos - Dillon, N. Lima; Campos, P. C. E. Oliveira de (My University, 1979)
50 patients with pyogenic infections of the skin were divided into 2 groups and treated with cephalexin. Group A, 26 patients, received 500 mg/12 hours; Group B, 24 patients, 250 mg/6 hours. Clinical diagnosis was substantiated by bacteriologic study of cultures to identify the organism and determination of its susceptibility to the drug. Group A showed 91%, group B 95%; satisfactory results. No side-effects were noted. Either form of dosage was effective in the treatment of pyogenic infections of the skin.
Cephalexin in pyogenic infections of the skin: comparison of two therapeutic regimens
Keywords: cefalexin; acne; dermatitis; drug dose; drug therapy; impetigo; pyoderma; skin infection; therapy